2009
DOI: 10.3928/08910162-20090527-04
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Back Pain Among Farm Women in Southeast Louisiana

Abstract: This cross-sectional survey details the incidence and predictors of self-reported back pain among farm women from southeastern Louisiana. The sample was obtained from a preexisting data set of a cross-sectional randomized sample of farm women who participated in the Louisiana Farm Family Injury Prevention and Health Initiative research project. The Haddon Injury Model was used as the conceptual framework. Approximately one fourth of the women in the sample reported back pain in the past year. The major finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…The present study found that LBP was higher in females compared to males. This is consistent with the previously reported studies [3,10,11,12,13,22,23,24] that showed that LBP symptoms were consistently more common among females. Schneider et al [13] and Hathorn et al [24] stated that the risk of LBP is higher among females due to the stress of hormonal changes, gynaecological problems and childbirth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study found that LBP was higher in females compared to males. This is consistent with the previously reported studies [3,10,11,12,13,22,23,24] that showed that LBP symptoms were consistently more common among females. Schneider et al [13] and Hathorn et al [24] stated that the risk of LBP is higher among females due to the stress of hormonal changes, gynaecological problems and childbirth.…”
Section: Discussionsupporting
confidence: 93%
“…The present study also disclosed significant correlations between the frequency of LBP and socio-demographic factors, which is in accordance with earlier observations [1,2,3,4,10,11,12,20,21,22,23,24,25,26]. It is possible that LBP is more likely to be reported by those with a lower economic index and lower educational qualifications [3].…”
Section: Discussionsupporting
confidence: 92%